Postpartum seizures with posterior reversible encephalopathy syndrome following cesarean delivery for triplets - Anita Chhabra; Sheetal Jagtap (Wolters Kluwer Medknow Publications, 2014)
Posterior reversible encephalopathy syndrome (PRES) is a recently described clinicoradiologic entity that is associated with several medical conditions like hypertensive encephalopathy and eclampsia. It presents with rapid onset of symptoms including headache, seizures, altered consciousness, and visual disturbance. It is often, but not always associated with high blood pressure. We present a case of 23-year-old patient, with unremarkable antenatal period, who developed convulsions in the immediate postpartum period following elective cesarean delivery of her triplets performed under regional anesthesia. The magnetic resonance imaging brain revealed vasogenic edema suggestive of PRES. She was managed with supportive treatment including mechanical ventilation in the intensive care unit. She recovered completely without neurological sequelae and discharged on the 8 th postoperative day. This case report highlights the importance of awareness, prompt diagnosis and treatment to improve the outcome in this potentially life-threatening, but reversible condition.